تقييم بعض الصفات الإنتاجية لمجموعة من سلالات السمسم المطفرة فيزيائياً Sesamum indicum L. (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
The research aims at studying the different plant characteristics of mutant strains, selecting the best ones for adoption as new varieties or introducing them into breeding programs. The research was carried out at the Pine Research Station of the Center for Agricultural Scientific Research in Lattakia. The plant material included 21 mutant strains of sesamum in the fourth generation with the two main cultivars (Hourani and Zori). The results showed that the (9) cultivar was significantly higher in the number of branches per plant than the rest of the mutant strains and on the two (4) branches on the plant while the value of the two groups was Hourani and Zori (1, 2.75 branch / plant) respectively. As for the number of capsules on the plant, the strain (17) was significantly superior to the rest of the mutant strains and to the two witnesses (188.5 capsules), and the two researchers were Hourani and Zouri (72.5 and 80.5) capsules, respectively. The strain (17) significantly exceeded the length of the capsule on the rest of the breeds and the witness at a value of 4 cm. The value of the two witnesses was Hourani and Zouri (2.5, 2.25) respectively. As for plant height, the strain (17) significantly affected the rest of the mutant strains and the two witnesses at a value of (162.5 cm) while the height of the two witnesses Horani and Zuri (135 cm, 132.5 cm), respectively. As for the 1000-seed weight, strain (2) and its value (5.04 g) were the closest to the Hawrani strain (5.37 g), which exceeded all breeds, while the value of the witness was Zori (4.46 g). Also outperformed the strain (17) as a significant yield of pods /h on the rest of mutagens and strains on the value of two witnesses (8860 kg / h), this has reached the value of Hourani and witnesses Zori (6160, 6796.5 kg / h) respectively. The superiority of notes strain (19) morally as seeds / h yields on the rest of mutagens and strains on the value of two witnesses (2711.5 kg / h) were also strains (20-17-6-15-12) is superior to the two witnesses Hourani (2267 kg / h) and Zori (2356.5 kg / h). While the dressing was (62.5%) of the strain (14), which was significantly outperformed the rest of the mutagenic strains on witnesses Hourani and Zori who were worth (37, 34.5%) respectively. Thus, strains (19-20-17-6-15-12) that have been superior to seed yields can be adopted as new varieties or introduced into subsequent breeding programs. نُفذ البحث في محطة بحوث الصنوبر التابعة لمركز البحوث العلمية الزراعية باللاذقية، وتضمنت المادة النباتية 21 سلالة مطفرة من السمسم بالجيل الرابع مع الصنفين الأساسيين (حوراني و زوري). تم دراسة الصفات النباتية المختلفة للسلالات المطفرة، لانتخاب أفضلها واعتمادها لاحقاً كأصناف جديدة أو إدخالها في برامج التربية. تبيّن من خلال نتائج البحث أن السلالة (9) تفوقت معنوياً بصفة متوسط عدد الأفرع بالنبات على بقية السلالات المطفرة وعلى الشاهدين بقيمة (4) أفرع على النبات بينما بلغت قيمة الشاهدين حوراني وزوري (1، 2.75 فرع / النبات) على التوالي. أما بالنسبة لصفة عدد الكبسولات على النبات تبين أن السلالة (17) تفوقت معنوياً على بقية السلالات المطفرة وعلى الشاهدين بقيمة (188.5 كبسولة)، هذا وقد بلغت قيمة الشاهدين حوراني و زوري (72.5، 80.5) كبسولة على التوالي. هذا وقد تفوقت السلالة(17) معنوياً بصفة طول الكبسولة على بقية السلالات وعلى الشاهد بقيمة (4 سم)، هذا وقد كانت قيمة الشاهدين حوراني وزوري(2.5، 2.25) سم على التوالي. بالنسبة لصفة ارتفاع النبات تفوقت السلالة (17) معنوياً على بقية السلالات المطفرة وعلى الشاهدين بقيمة (162.5 سم) بينما بلغ ارتفاع الشاهدين حوراني و زوري (135 سم، 132.5سم) على التوالي. أما بالنسبة لصفة وزن ال1000 بذرة فقد تميزت السلالة (2) وقيمتها (5.04غ) بأنها الأقرب إلى صنف الشاهد حوراني(5.37غ) الذي تفوق على جميع السلالات، في حين بلغت قيمة الشاهد زوري (4.46غ). كما تفوقت السلالة (17) معنوياً بصفة غلة الكبسولات /ه على بقية السلالات المطفرة وعلى الشاهدين بقيمة (8860 كغ/ه) ، هذا وقد بلغت قيمة الشاهدين حوراني و زوري (6160، 6796.5 كغ/ه) على التوالي. ويُلاحظ تفوق السلالة (19) معنوياً بصفة غلة البذور/ ه على بقية السلالات المطفرة وعلى الشاهدين بقيمة (2711.5 كغ/ه) كما كانت السلالات (20-17-6-15-12) متفوقة على الشاهدين الحوراني (2267 كغ/ه) والزوري(2356.5 كغ/ه). بينما بلغت نسبة التصافي  (62.5 %) للسلالة (14) التي تفوقت معنوياً على بقية السلالات المطفرة وعلى الشاهدين حوراني وزوري الذين كانت قيمتهما (37، 34.5 %) على التوالي.